Implementasi Pendidikan Karakter Disiplin pada Ekstrakurikuler Hizbul Wathan di Sekolah Menengah Kejuruan - Nisrin Mu'azzaz; Karnadi (Cendekia, 2023)
The purpose of this research is to investigate how character education in discipline is implemented in the extracurricular activity 'Hizbul Wathan' at SMK Muhammadiyah 1 Semarang, as well as the contribution and impact generated from the application of character education in the discipline within the 'Hizbul Wathan' extracurricular at SMK Muhammadiyah 1 Semarang. This is a qualitative study, and the researcher collected data using interview and observation techniques. The Head of the Student Affairs Department and the coach or person in charge of the 'Hizbul Wathan' extracurricular at SMK Muhammadiyah 1 Semarang were among those interviewed. After the data was gathered, data analysis was conducted, followed by drawing conclusions. The research findings indicate that the 'Hizbul Wathan' extracurricular at SMK Muhammadiyah 1 Semarang contributes to the implementation of character education in the discipline. One form of implementing character education in discipline carried out by SMK Muhammadiyah 1 Semarang is by establishing rules and regulations for the students, providing a role model, and consistently enforcing the rules. By implementing character education in the discipline of the 'Hizbul Wathan' extracurricular, it is expected that this extracurricular activity can actively play a role in shaping quality discipline in its members, enabling them to become disciplined and influential individuals in the future.